Quantitative EEG, Cognitive Deficits, and BECTS - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Researchers at Pontificia Universidade Catolica, Campinas, Brazil studied the relationship between educational problems and clinical/EEG aspects of benign childhood epilepsy with centrotemporal spikes (BECTS) in 38 children, ages 8 to 11 years (average age 9.29 +/- 1.27).